Implementation of Operational Strategy Planning in Arena Corner Business - Taryana Taryana; Tantri Yanuar Rahmat Syah; Diana Fajarwati; Rhian Indradewa (Journal of Multidisciplinary Academic, 2021)
In a business plan, the Operational role cannot be underestimated. The pace of the business will be fast if the operational department implements the right and accurate strategy in executing all operational aspects in increasing the pace of business, like wise in the Arena Corner business plan, a precise operational strategy is needed so that other parts feel the operational locomotive moving all aspects of the business. This study aims to determine the importance of a start-up application's operational part in managing the company's operations. This study aims to determine the importance of a start-up application's operational part in managing the company's operations. The conclusion of this study is the need for Section operational conduct deployment strategy up to date and out of the box to get a significant impact from implementing these strategies.